(untitled) - Schmidt, Dodi-Katrin (Hoboken, NJ, 2004)
This book guide readers how to get directions, shop, and eat out; talk numbers, dates, time, and money; chat about family and work; discuss sports and the weather; deal with problems and emergencies by French
Keywords: French language,Tiếng Pháp thực hành; Conversation and phrase books